2018
DOI: 10.1098/rsos.180469
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural differences in implicit learning of chunks versus symmetries

Abstract: Three experiments explore whether knowledge of grammars defining global versus local regularities has an advantage in implicit acquisition and whether this advantage is affected by cultural differences. Participants were asked to listen to and memorize a number of strings of 10 syllables instantiating an inversion (i.e. a global pattern); after the training phase, they were required to judge whether new strings were well formed. In Experiment 1, Western people implicitly acquired the inversion rule defined ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 78 publications
0
11
1
Order By: Relevance
“…The relevant behavioural and simulation results demonstrated that both surface and abstract structures can be captured by this dual process model, but abstract structures can be learned only explicitly. However, this is inconsistent with recent findings that people can implicitly acquire abstract structures ( Lin and Murray, 2013 ; Tanaka and Watanabe, 2014a , b , 2015 ; Huang et al, 2017 ; Fu et al, 2018 ; Ling et al, 2018 ).…”
Section: Introductioncontrasting
confidence: 92%
See 2 more Smart Citations
“…The relevant behavioural and simulation results demonstrated that both surface and abstract structures can be captured by this dual process model, but abstract structures can be learned only explicitly. However, this is inconsistent with recent findings that people can implicitly acquire abstract structures ( Lin and Murray, 2013 ; Tanaka and Watanabe, 2014a , b , 2015 ; Huang et al, 2017 ; Fu et al, 2018 ; Ling et al, 2018 ).…”
Section: Introductioncontrasting
confidence: 92%
“…Moreover, the present findings also helped account for the inconsistent findings about abstract learning and consciousness. Although more recent studies have provided new evidence that abstract learning can occur unconsciously ( Dienes et al, 2012 ; Kemeny and Meier, 2016 ; Huang et al, 2017 ; Ling et al, 2018 ), other studies supported that abstract knowledge can only be acquired consciously ( Shanks and St John, 1994 ; Dominey et al, 1998 ; Boyer et al, 2005 ; Cleeremans and Destrebecqz, 2005 ). According to our findings, this might be because the former studies used relatively simple abstract structures while the latter studies used more complex structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fu, Dienes & Fu, 2010), symmetry learning (e.g. Jiang, Zhu, Guo, Ma, Yang & Dienes, 2012;Ling et al, 2018), second language learning (e.g. Paciorek & Williams, 2015;Rebuschat, 2013;Rogers, Revesz, & Rebuschat, 2016), probabilistic category learning (e.g., Kemény & Lukács, 2013), learning conjunctive rule sets (Neil & Higham, 2012), and learning multiple grammars (Wan, Dienes, & Fu, 2008;Norman, Scott, Price, Jones, & Dienes, in press).…”
Section: Subjective Measures Of Awareness In Implicit Learningmentioning
confidence: 99%
“…This method has been most commonly applied in AGL, where it has shown that participants acquire, not only conscious, but also unconscious (structural) knowledge of the grammars, since they respond accurately when they rely on unconscious structural knowledge (Guess, Intuition, Familiarity) (e.g., Dienes & Scott, 2005;Norman & Price, 2012;Norman et al, 2016Norman et al, , 2019Scott & Dienes, 2008. Similar results with this method have been found in evaluative conditioning (Jurchis et al, 2020;Waroquier et al, 2020), implicit sequence learning (Fu et al, 2012(Fu et al, , 2018Zhang & Liu, 2021), language learning (e.g., Paciorek & Williams, 2015;Zhao et al, 2021), symmetry learning (Jiang et al, 2012;Ling et al, 2018), learning of conjunctive rules (Neil & Higham, 2012, or implicit social learning (Costea, 2018;Costea et al, 2020).…”
Section: Figurementioning
confidence: 75%